2013
DOI: 10.1080/02640414.2013.815360
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the exercise intensity that elicits maximal fat oxidation in short-time testing

Abstract: Maximal fat oxidation (MFO) rate and the exercise intensity that elicits MFO (FATmax-intensity) were designed to evaluate fat metabolism capacity and to provide individuals with a target exercise intensity during prolonged exercise. However, the previous methods of determining FATmax-intensity were time-consuming. The purpose of this study was to examine the validity of FATmax-intensity determined by short-time testing. Nine healthy young men performed ramp exercise, in a short-time test, until exhaustion and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
(32 reference statements)
0
26
0
Order By: Relevance
“…However, while more strict pre-test standardization leads to greater internal validity, it also leads to poorer external validity (i.e harder translation of the results into practice). More generally, while the validity of using a graded exercise tests to determine Fat max has been reported in a number of studies [3], [13], [33], [34], a recent study questions the usefulness using this approach to prescribe training in populations such as highly trained athletes [35]”.…”
Section: Discussionmentioning
confidence: 99%
“…However, while more strict pre-test standardization leads to greater internal validity, it also leads to poorer external validity (i.e harder translation of the results into practice). More generally, while the validity of using a graded exercise tests to determine Fat max has been reported in a number of studies [3], [13], [33], [34], a recent study questions the usefulness using this approach to prescribe training in populations such as highly trained athletes [35]”.…”
Section: Discussionmentioning
confidence: 99%
“…The main variations involve alterations in exercise intensities (eg, increments of 35 W vs 20 W) 8,48 or stage durations (eg, stage duration of 1 minute vs 10 minutes). 31,49 Nowadays, there is no consensus about which is the best stage duration to estimate MFO and Fat max . The application of too large workload increments and short stage durations may lose accuracy on MFO and Fat max estimation and do not ensure that the participant reaches steadystate gas exchange measure in each stage.…”
Section: Graded Exercise Protocolmentioning
confidence: 99%
“…Bircher et al [4] reported that the protocol that was more time-consuming indicated a higher Fatmax and MFO than those done by a shorter protocol, although the increments for both protocols were small. These data indicated that Fatmax may be influenced by exercise duration, probably due to changes in substrate concentrations and hormonal responses [15]. In contrast, Achten et al [1] concluded that exercise duration did not affect Fatmax determination.…”
Section: Introductionmentioning
confidence: 96%
“…It is known that exercise intensity is one of the main factors determining the rate of fat oxidation during exercise [2]. Absolute fat oxidation rates increase during low-to-moderate exercise intensities and then markedly decline at high intensities, implying that there is an exercise intensity at which the rate of fat oxidation is maximal (Fatmax) [15]. The highest rate of fat oxidation during submaximal exercise has been reported to occur between 40 and 65% of peak oxygen consumption (VO2peak) [1].…”
Section: Introductionmentioning
confidence: 99%